Preparation method and application of powdery modified aramid nano composite filler

Through the combination of modified aramid nanofibers and functionalized silica nanoparticles, the problems of uneven dispersion and poor interfacial performance in the polymer matrix are solved, and the significant mechanical properties of the composite material are improved.

CN119463299AActive Publication Date: 2025-02-18QINGDAO UNIV OF SCI & TECH

Patent Information

Application Number
CN202411819575.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-18
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The uniform dispersion of aramid nanofibers in polymer matrix shows limitations, prone to agglomeration, and there is a lack of effective filler-matrix interaction between the fibers and the matrix, resulting in poor mechanical properties of composite materials.

Method used

Functionalized silica nanoparticles were prepared by specific stirring and reaction treatment of components such as water-soluble polymers, aramid nanofiber hydrogels, alkoxysilane compounds and silicate compounds. Aramid nanocomposite filler forms powder-like modified products.

Benefits of technology

This method enables the modified aramid nanofibers to form good dispersion in the polymer matrix, significantly improving the interface performance of the composite material. For example, in some applications, tensile strength is increased by 1200%, fixed extension stress is increased by 1357%, and the Wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463299A_ABST
    Figure CN119463299A_ABST
Patent Text Reader

Abstract

The invention provides a powdery modified aramid nanofiber filler as well as a preparation method and application thereof, and belongs to the technical field of composite materials. The method provided by the invention comprises the following steps: firstly, adding a water-soluble high polymer into a solvent, then adding nano aramid fiber hydrogel into the solution, and finally, respectively adding an alkoxy silane compound and a silicate compound into the solution to obtain the powdery modified aramid nano composite filler with functionalized silicon dioxide nanoparticles grafted on the surface. The modified aramid nano composite filler prepared by the invention is powdery solid filler, is easy to industrialize, and can be applied as nano composite filler of a polymer composite material. According to the prepared modified aramid nano composite filler / polymer composite material, the problem that the aramid nano fibers are difficult to disperse in the polymer is effectively solved, and more importantly, the physical and mechanical properties of the composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a powdered modified aramid nanofiber filler and a preparation method and application thereof. Background Art

[0002] Aramid nanofibers have the structural characteristics of high aspect ratio and high specific surface area, and on the other hand, they also maintain the excellent mechanical, chemical corrosion resistance and thermal durability properties of poly(p-phenylene terephthalamide) (PPTA) fibers. As one of the most prominent reinforcing materials in various high-performance polymer composites such as aerospace, bulletproof materials, and building materials, it has attracted great attention in the field of nanocomposites and has been widely used in the research and application of polymer composite reinforcement, high-performance aviation, military equipment and other material fields.

[0003] Although aramid nanofibers have structural advantages at the nanoscale, they are chemically inert due to the highly oriented internal molecular chains and the strong interactions between aromatic rings through π-π stacking conjugation, which adds challenges to the modification of aramid nanofibers. The uniform dispersion of aramid nanofibers in the matrix is ​​limited and they are prone to agglomeration, which hinders the complete recovery of the nanomorphology of aramid nanofibers. In addition, there is a lack of effective filler-matrix interaction between the fiber and the matrix, that is, the weak interfacial bonding between the aramid nanofiber and the matrix leads to poor mechanical properties of the composite material. Therefore, how to increase the contact area between the fiber and the matrix, so that it can be well dispersed in the polymer matrix and improve the interfacial properties of the composite material is a problem that needs to be solved at present. Summary of the invention

[0004] The purpose of the present invention is to provide a powdered modified aramid nanofiber filler and a preparation method and application thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] First, the present invention provides a method for preparing a powdered modified aramid nanocomposite filler, the method comprising the following steps:

[0007] (1) adding a water-soluble polymer to a solvent A, stirring and dissolving the mixture to obtain a mixed solution A;

[0008] (2) adding the aramid nanofiber hydrogel to the mixed solution A, adding the alkoxysilane compound during the stirring process, and continuing to stir evenly to obtain a mixed solution B;

[0009] (3) dispersing the silicate compound in solvent B, adding the mixture to the mixed solution B, and continuing to stir the reaction to obtain a modified aramid nanocomposite filler dispersion with grafted functionalized silica nanoparticles;

[0010] (4) After vacuum-assisted filtration of the modified aramid nanocomposite filler dispersion, the obtained solid is washed and placed in a vacuum oven for drying to obtain a powdered modified aramid nanocomposite filler.

[0011] Preferably, for every 20-56g of the water-soluble polymer, the corresponding amount of solvent A is 50-500mL, the corresponding amount of aramid nanofiber hydrogel is 1.54-15.5g, the corresponding amount of alkoxysilane compound is 4-35mL, the corresponding amount of silicate compound is 1.7-20mL, and the corresponding amount of solvent B is 0.9-8.5mL.

[0012] Preferably, in step (1), the water-soluble polymer is at least one of strongly hydrophilic polymers containing polar nonionic groups;

[0013] The diameter of the aramid nanofiber in the aramid nanofiber hydrogel is 10-300 nm, and the content of the aramid nanofiber is 1-10 wt %;

[0014] The solvent A is at least one of deionized water, ethanol, propanol, acetone, butanone, tetrahydrofuran, n-butanol, ethyl acetate, dimethylformamide, dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone;

[0015] Preferably, the strongly hydrophilic polymer includes one or more of polyethylene glycol monomethyl ether, polyethylene glycol, polyethylene oxide, and polyvinyl pyrrolidone.

[0016] Preferably, in step (2), the alkoxysilane compound is a mixture of one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane;

[0017] Preferably, in step (3), the silicate compound is a mixture of one or more of ethyl orthosilicate, butyl orthosilicate, propyl orthosilicate and isopropyl orthosilicate;

[0018] The solvent B is a mixture of one or more of deionized water, ethanol, propanol, acetone, butanone, tetrahydrofuran, n-butanol, ethyl acetate, dimethylformamide, dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.

[0019] Preferably, in step (3), the device is a mechanical stirring device, the stirring reaction time is 0.5-8 hours; and the reaction temperature is room temperature-60°C.

[0020] Secondly, the present invention provides a powdered modified aramid nanocomposite filler, which is prepared by the above-mentioned preparation method.

[0021] The invention provides application of powdered modified aramid nanocomposite filler in preparing modified polymer composite material. The polymer in the modified polymer composite material is a mixture of one or more polar or non-polar polymers.

[0022] Preferably, the polymer is a mixture of one or more polymers containing benzene rings or polar groups.

[0023] Preferably, the polymer is at least one of a polymer containing a benzene ring, an ester group, an ether group, a hydroxyl group, a cyano group, an amide group, a halogen group, a carboxyl group, and a carbonate group.

[0024] Preferably, the polymer is a mixture of one or more of styrene-butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, acrylic rubber, ethylene-vinyl acetate rubber, polycarbonate, polyurethane, polytetrafluoroethylene, epoxy resin, and polyvinyl alcohol.

[0025] Preferably, the application is to mix the modified aramid nanofiber composite filler with a polymer, and vulcanize (hot press) the modified aramid nanofiber / polymer composite material to obtain a modified aramid nanofiber / polymer composite material with significantly improved tensile strength and tensile stress;

[0026] Or the application is to mix (mix) the modified aramid nanofiber composite filler with polymer and white carbon black, and vulcanize (hot press) it to obtain a modified aramid nanofiber / white carbon black reinforced polymer composite material with significantly improved tensile strength, tensile stress and wear resistance.

[0027] The beneficial effects of the present invention are:

[0028] The invention provides a preparation method of aramid nanofiber modified by powdered filler. The method enables aramid nanofiber modified by functionalized silicon dioxide nanoparticles to be well dispersed in a polymer matrix as a nanofiller through the interface action between the silicon dioxide-reinforced aramid nanofiber and a polymer, thereby overcoming the problem that ordinary aramid nanofibers cannot be processed by direct mechanical blending and are prone to agglomeration and uneven dispersion in the polymer. The method is applied to the preparation of polymer composite materials to improve the physical and mechanical properties of the polymer materials. For example, by adding 5phr of modified aramid nanocomposite filler, the tensile strength of the composite material can be increased by 1200% compared with a polymer to which no modified aramid nanocomposite filler is added, and the 300% elongation modulus is increased by 1357%; by adding only 2.5phr of modified aramid nanocomposite filler to a polymer matrix reinforced with white carbon black, the tensile strength of the composite material can be increased by 30% compared with the polymer reinforced with white carbon black, the 300% elongation modulus is increased by 58%, and the DIN wear resistance is increased by 25%. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 TEM photos of (a) aramid nanofibers before modification and (b) modified aramid nanocomposite filler a in Example 1;

[0030] Figure 2 The figures are (a) aramid nanofiber hydrogel and (b) the modified aramid nanocomposite filler b in Example 2;

[0031] Figure 3 The thermogravimetric analysis diagram of aramid nanofiber and modified aramid nanocomposite filler b in Example 2;

[0032] Figure 4 The SEM images of the polymer composite materials of (a) Example 6 and (b) Comparative Example 2 are shown;

[0033] Figure 5 This is an electronic photograph of the cross-section of the mixed rubber of the aramid nanofiber / rubber composite material 1 in Comparative Example 3. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0035] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0036] In the present invention, "aramid nanofibers" include meta-aramid fibers and para-aramid fibers with or without other comonomers.

[0037] Para-aramid, poly(p-phenylene terephthalamide) (PPTA), also known as aramid 1414, is a linear high molecular polymer in which more than 85% of the amide bonds in the molecular chain are directly bonded to the aromatic ring. It has a simple and symmetrical structure, regular arrangement, a diameter between 10 and 100 nm, and an aspect ratio of about 3000. In addition to the characteristics of high strength, high modulus, high temperature resistance, and corrosion resistance, it has a large specific surface area, high surface energy, good dispersibility, high water retention rate, and excellent flame retardant properties. Due to its excellent properties, para-aramid nanofibers have broad application prospects in the fields of composite reinforcement, battery separators, adsorption filtration, electrical insulation, and flexible electrodes.

[0038] Meta-aramid, namely poly(m-phenylene isophthalamide) (PMTA), is also known as aramid 1313. Meta-aramid is the fastest growing seed in organic high temperature resistant fiber. The fiber molecules are composed of meta-phenyl groups connected by amide groups. The molecular chain is linear and serrated, with low knotting and orientation. Therefore, its strength and modulus are not as good as those of para-aramid. However, due to the strong hydrogen bonding between molecules, the fiber has excellent flame retardancy, thermal stability, radiation resistance and other properties.

[0039] In the present invention, "aramid nanofiber hydrogel" refers to a hydrogel structure formed by aramid nanofibers, wherein the content of aramid nanofibers is 2-5wt%. This hydrogel structure can be directly generated during the in-situ synthesis of aramid nanofibers, or can be a hydrogel formed by dry aramid fibers through technical means.

[0040] The materials used in the present invention are listed in Table 1:

[0041] Table 1 Basic raw materials used in the present invention

[0042]

[0043] The analytical tests performed by the present invention are as follows:

[0044] TEM test: The microstructure of the nanofibers was tested using a JEM-2100 transmission electron microscope (manufactured by JEOL Ltd, Japan).

[0045] TGA test: Thermogravimetric analysis was performed using a TGA 2 thermogravimetric analyzer (manufactured by METTLER TOLEDO Ltd, USA) with a heating rate of 10 K / min, a temperature range of room temperature to 900° C., and a nitrogen atmosphere.

[0046] SEM test: The SEM spectra of the polymer composites were measured using a JSM7500F scanning electron microscope (manufactured by JEOL Ltd, Japan), and the test samples were brittle fracture surfaces of tensile specimens.

[0047] Polymer tensile strength test: The tensile strength of the polymer composite material was measured using a Model Z005 electronic tensile testing machine (manufactured by Zwick Ltd, Germany) according to DIN 53504 implementation standard, with a tensile speed of 500 mm / min and a temperature of room temperature.

[0048] Example 1

[0049] Preparation of modified aramid nanofiber composite filler

[0050] (1) adding 56 g of polyethylene glycol monomethyl ether to 300 mL of n-butanol, stirring at 30° C. and 500 rpm for 30 minutes to obtain a mixed solution A1;

[0051] (2) 15.5 g of para-aramid nanofiber hydrogel (aramid nanofiber solid content: 3%) was added to the mixed solution A1, 20 mL of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added during stirring, and stirring was continued for 1 hour to obtain a mixed solution B1;

[0052] (3) dispersing 10 mL of butyl orthosilicate in 5 mL of n-butanol solvent, and adding the mixture to the mixed solution B1 to obtain functionalized silica nanoparticles. After stirring for 6 hours using a device, a modified aramid composite filler dispersion with grafted functionalized silica nanoparticles was obtained;

[0053] (4) vacuum-assisted filtration, washing twice with ethanol and once with deionized water, and drying in a vacuum oven for 8 hours to obtain a powdered modified aramid nanocomposite filler a.

[0054] The powdered modified aramid nanocomposite filler a prepared by the method of the present invention is in a highly dispersed state of ultrafine particles.

[0055] First, transmission electron microscopy was used to detect the differences between aramid nanofibers before and after modification. The results are as follows: Figure 1 shown.

[0056] from Figure 1 It can be seen that on the modified aramid nanocomposite filler a, the silica nanoparticles are evenly distributed on the surface of the aramid nanofibers.

[0057] Next, the present invention performs a thermogravimetric analysis on the modified aramid nanofiber powder filler, and the obtained silicon dioxide content is 28.8wt%.

[0058] Example 2

[0059] Preparation of modified aramid nanofiber composite filler b

[0060] (1) Add 50 g of polyethylene glycol to 300 mL of ethanol, and stir at 30° C. and 500 rpm for 30 minutes to obtain a mixed solution A2;

[0061] (2) 9.26 g of para-aramid nanofiber hydrogel (aramid nanofiber solid content: 3%) was added to the mixed solution A2, 18 mL of γ-aminopropyltriethoxysilane was added during stirring, and stirring was continued for 1 hour to obtain a mixed solution B2;

[0062] (3) dispersing 10 mL of tetraethyl orthosilicate in 5 mL of ethanol solvent, and adding the mixture to the mixed solution B2 to obtain functionalized silica nanoparticles. After stirring for 6 hours using a device, a modified aramid nanocomposite filler dispersion with grafted functionalized silica nanoparticles was obtained;

[0063] (4) vacuum-assisted filtration, washing twice with ethanol and once with deionized water, and drying in a vacuum oven for 8 hours to obtain a powdered modified aramid nanocomposite filler b.

[0064] The powdered modified aramid nanocomposite filler b prepared by the present invention is as follows Figure 2 (b) as shown.

[0065] Next, the present invention performs thermogravimetric analysis on the modified aramid nanofiber powder filler. Figure 3 As shown, the obtained silica content is 31.6 wt%.

[0066] Example 3

[0067] Preparation of modified aramid nanofiber composite filler c

[0068] (1) adding 20 g of polyvinyl alcohol to 50 mL of propanol, stirring at 30° C. and 500 rpm for 30 minutes to obtain a mixed solution A3;

[0069] (2) 1.54 g of para-aramid nanofiber hydrogel (aramid nanofiber solid content: 3%) was added to the mixed solution A3, 4 mL of γ-methacryloxypropyltrimethoxysilane was added during stirring, and stirring was continued for 1 hour to obtain a mixed solution B3;

[0070] (3) dispersing 1.7 mL of propyl orthosilicate in 0.9 mL of propanol solvent, and adding the mixture to the mixed solution B3 to obtain functionalized silica nanoparticles. After stirring for 6 hours using a device, a modified aramid nanocomposite filler dispersion with grafted functionalized silica nanoparticles was obtained;

[0071] (4) vacuum-assisted filtration, washing twice with ethanol and once with deionized water, and obtaining the modified aramid nanocomposite filler c after filtration.

[0072] The present invention performs thermogravimetric analysis on the powdery modified aramid nanocomposite filler C, and obtains a silicon dioxide content of 28.2wt%.

[0073] Example 4

[0074] Preparation of modified aramid nanofiber composite filler

[0075] (1) adding 35 g of polyvinyl pyrrolidone to 500 mL of dimethylformamide, stirring at 30° C. and 500 rpm for 30 minutes to obtain a mixed solution A4;

[0076] (2) 15.5 g of meta-aramid nanofiber hydrogel (aramid nanofiber solid content: 3%) was added to 300 mL of dimethylformamide, 35 mL of γ-mercaptopropyltriethoxysilane was added during stirring, and stirring was continued for 1 hour to obtain a mixed solution B4;

[0077] (2) dispersing 20 mL of tetraethyl orthosilicate in 8.5 mL of dimethylformamide solvent, and adding the mixture to the mixed solution B4 to obtain silica nanoparticles. After stirring for 6 hours using a device, a modified aramid nanocomposite filler dispersion of grafted silica nanoparticles was obtained;

[0078] (3) vacuum-assisted filtration, washing twice with ethanol and once with deionized water, and drying in a vacuum oven for 8 hours to obtain a powdered modified aramid nanocomposite filler d.

[0079] The present invention conducts thermogravimetric analysis on the modified aramid nanofiber powder filler, and the obtained silicon dioxide content is 26.9wt%.

[0080] Example 5

[0081] Preparation of modified aramid nanofiber / rubber composites 1

[0082] (1) 100 phr of styrene-butadiene rubber, 5 phr of modified aramid nanocomposite filler a, 1 phr of antioxidant 4020, 1 phr of antioxidant RD, 3 phr of zinc oxide, and 1 phr of stearic acid were mixed in an internal mixer at 100±5° C. for 6 minutes to obtain an internal mixer;

[0083] (2) mixing the internal rubber and the vulcanizing agent (sulfur 2 phr, accelerator CZ 1.6 phr, accelerator D 1.5 phr) on an open mixer, and thinning the mixture 5 times before sheeting to obtain a mixed rubber;

[0084] (3) The mixed rubber is vulcanized at a specific t90, 160° C. to obtain a vulcanized rubber, i.e., composite material 1.

[0085] The tensile strength test results show that when 5phr modified aramid nanocomposite filler a is added to the polymer matrix, the tensile strength of the composite material can be increased by 1200% compared with the polymer without modified aramid nanocomposite filler a, and the 300% elongation stress is increased by 1357%.

[0086] Example 6

[0087] Preparation of modified aramid nanofiber / rubber composites 2

[0088] (1) 100 phr of styrene-butadiene rubber, 2.5 phr of modified aramid nanofiber composite filler a, 1 phr of antioxidant 4020, 1 phr of antioxidant RD, 3 phr of zinc oxide, 1 phr of stearic acid, 50 phr of white carbon black, 4 phr of silane coupling agent Si69 and 10 phr of aromatic oil were mixed in an internal mixer at 100±5° C. for 6 minutes to obtain an internal mixer;

[0089] (2) Mix the rubber at 140±5°C for 5 minutes;

[0090] (3) Mixing the internal rubber and the vulcanizing agent (sulfur 2phr, accelerator CZ 1.6phr, accelerator D 1.5phr) on an open mixer, and thinning the mixture 5 times before sheeting to obtain a mixed rubber;

[0091] (4) The mixed rubber is vulcanized at a specific t90, 160°C to obtain a vulcanized rubber, i.e., composite material 2.

[0092] The tensile strength test results show that by adding only 2.5phr modified aramid nanocomposite filler a to the polymer matrix reinforced with silica, the tensile strength of the composite material can be increased by 30% compared with the polymer reinforced with silica; the 300% tensile stress is increased by 58%; and the DIN abrasion results show that the wear resistance is improved by 25%.

[0093] In addition, if Figure 4 As shown in (a), the scanning electron microscopy of the brittle fracture surface of the composite material shows that the modified aramid nanofibers are uniformly dispersed in the polymer matrix, and the interfacial interaction between the fibers and the rubber matrix is ​​improved.

[0094] Example 7

[0095] Preparation of modified aramid nanofiber / rubber composites 3

[0096] (1) 100 phr of nitrile rubber, 5 phr of modified aramid nanocomposite filler b, 1 phr of antioxidant 4020, 1 phr of antioxidant RD, 5 phr of zinc oxide, and 1 phr of stearic acid were mixed in an internal mixer at 100±5° C. for 6 minutes to obtain an internal mixer;

[0097] (2) mixing the internal rubber and the vulcanizing agent (sulfur 1.5 phr, accelerator DM 1.5 phr) on an open mixer, and thinning through 5 times before sheeting to obtain a mixed rubber;

[0098] (3) The mixed rubber is vulcanized at a specific t90, 160°C to obtain a vulcanized rubber, i.e., composite material 3.

[0099] The tensile strength test results show that when 5phr modified aramid nanocomposite filler b is added to the polymer matrix, the tensile strength of the composite material is increased by 1095% compared with the polymer without modified aramid nanocomposite filler b, and the 300% elongation stress is increased by 1136%.

[0100] Example 8

[0101] Preparation of modified aramid nanofiber / rubber composites 4

[0102] (1) 100 phr of chloroprene rubber, 5 phr of modified aramid nanocomposite filler c, 1 phr of antioxidant 4020, 1 phr of antioxidant RD, 5 phr of NA-22, and 1 phr of stearic acid were mixed in an internal mixer at 100±5° C. for 6 minutes to obtain an internal mixer;

[0103] (2) mixing the internal rubber and the vulcanizing agent (4 phr of magnesium oxide and 5 phr of magnesium oxide) in an open mixer, and thinning the mixture 5 times before sheeting to obtain a mixed rubber;

[0104] (3) The mixed rubber is vulcanized at a specific t90, 160°C to obtain a vulcanized rubber, i.e., composite material 4.

[0105] The tensile strength test results show that when 5phr modified aramid nanocomposite filler b is added to the polymer matrix, the tensile strength of the composite material is increased by 262% compared with the polymer without adding modified aramid nanocomposite filler c, and the 300% elongation stress is increased by 553%.

[0106] Example 9

[0107] Preparation of modified aramid nanofiber / rubber composites 5

[0108] (1) 100 phr of hydrogenated nitrile rubber, 2.5 phr of modified aramid nanofiber composite filler a, 1 phr of antioxidant 445, 1 phr of antioxidant RD, 5 phr of zinc oxide, 1 phr of stearic acid, 50 phr of white carbon black, 4 phr of silane coupling agent Si69 and 10 phr of dibutyl phthalate were mixed in an internal mixer at 100±5° C. for 6 minutes to obtain an internal mixer;

[0109] (2) mixing the internal rubber and the vulcanizing agent (sulfur 1.5 phr, accelerator DM 2 phr) on an open mixer, and thinning through 5 times before sheeting to obtain a mixed rubber;

[0110] (3) The mixed rubber is vulcanized at a specific t90, 160°C to obtain a vulcanized rubber, i.e., composite material 5.

[0111] The tensile strength test results show that when 5phr of modified aramid nanocomposite filler b is added to the polymer matrix, the tensile strength of the composite material is increased by 23%, the 300% elongation stress is increased by 36%, and the wear resistance is increased by 15% compared with the polymer without modified aramid nanocomposite filler b.

[0112] Example 10

[0113] Preparation of modified aramid nanofiber / rubber composites 6

[0114] (1) 50 phr of polyisocyanate (component A), 50 phr of polyether polyol (component B), 2 phr of modified aramid nanocomposite filler d, antioxidant 4020 (1 phr), and antioxidant RD (1 phr) were mixed in an internal mixer at 100±5° C. for 6 minutes to obtain an internal compound rubber;

[0115] (2) The mixed rubber is pressed and solidified at room temperature to obtain a polyurethane composite material 6.

[0116] The tensile strength test results show that when 2phr modified aramid nanocomposite filler d is added to the polymer matrix, the tensile strength of the composite material is increased by 353%, the 300% tensile stress is increased by 475%, and the wear resistance is increased by 310% compared with the polymer without modified aramid nanocomposite filler d.

[0117] Embodiment 11

[0118] Preparation of modified aramid nanofiber / resin composites7

[0119] (1) 100 phr of epoxy resin, 2 phr of modified aramid nanocomposite filler b, and antioxidant 1010 were mixed in an internal mixer at 160±5° C. for 6 minutes to obtain a mixture;

[0120] (2) The mixture was pressed into a sheet at 160° C. for 10 min to obtain the epoxy resin composite material 7.

[0121] The tensile strength test results show that when 2.5phr modified aramid nanocomposite filler a is added to the polymer matrix, the tensile strength of the composite material is increased by 33% compared with the epoxy resin polymer without the modified aramid nanocomposite filler a, and the wear resistance is increased by 21%.

[0122] Comparative Example 1

[0123] Preparation of modified aramid nanofiber composite filler

[0124] (1) 9.26 g of aramid nanofiber hydrogel was added to n-butanol, 20 mL of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added during stirring, and stirring was continued for 1 hour to obtain a mixed solution A5;

[0125] (2) dispersing 10 mL of butyl orthosilicate in 5 mL of n-butanol solvent, and adding the mixture to the mixed solution B5 to obtain functionalized silica nanoparticles. After stirring for 6 hours using a device, a modified aramid composite filler dispersion with grafted functionalized silica nanoparticles was obtained;

[0126] (3) vacuum-assisted filtration, washing twice with ethanol and once with deionized water, and drying in a vacuum oven for 8 hours to obtain a powdered modified aramid nanocomposite filler e.

[0127] During the preparation of Comparative Example 1, no water-soluble polymer was added.

[0128] Comparative Example 2

[0129] Preparation of aramid nanocomposite fillers

[0130] (1) adding 56 g of polyethylene glycol monomethyl ether to 300 mL of n-butanol, stirring at 30° C. and 500 rpm for 30 minutes to obtain a mixed solution A6;

[0131] (2) 9.26 g of aramid nanofiber hydrogel was added to the mixed solution A6, and vacuum-assisted filtration was performed. The mixed solution was washed twice with ethanol and once with deionized water, and dried in a vacuum oven for 8 hours to obtain a block of aramid nanocomposite filler f.

[0132] Since no alkoxysilane compounds and silicate compounds were added during the preparation of Comparative Example 2, the blocky aramid nanocomposite filler f prepared by the method of the present invention exhibited ultra-high hardness, could not be formed into a powdery sample, and could not be dispersed through subsequent mixing processing.

[0133] Comparative Example 3

[0134] Preparation of aramid nanofiber / rubber composites 1

[0135] (1) 100 phr of styrene-butadiene rubber, 25 phr of unmodified aramid nanofiber hydrogel (solid content 3%, i.e., containing 0.75 phr of pure aramid nanofiber), 1 phr of antioxidant 4020, 1 phr of antioxidant RD, 3 phr of zinc oxide, 1 phr of stearic acid, 50 phr of white carbon black, 4 phr of silane coupling agent Si69 and 10 phr of aromatic oil were mixed in an internal mixer at 100±5° C. for 6 minutes to obtain an internal mixer;

[0136] (2) Mix the rubber at 140±5°C for 5 minutes;

[0137] (3) mixing the internal rubber and the vulcanizing agent in an open mixer, and thinning the mixture 5 times before sheeting to obtain a mixed rubber;

[0138] (4) vulcanizing the rubber mixture at a specific t90, 160° C. to obtain a vulcanized rubber, i.e., the aramid nanofiber / rubber composite material 1.

[0139] like Figure 5 As shown, aramid nanofiber aggregates are clearly visible inside the rubber compound with the naked eye, and the unmodified aramid nanofibers cannot be mixed and dispersed evenly in the polymer matrix by conventional mixing methods.

[0140] Comparative Example 4

[0141] Preparation of modified aramid nanofiber / rubber composites7

[0142] (1) 100 phr of styrene-butadiene rubber, 2.5 phr of modified aramid nanofiber composite filler e, 1 phr of antioxidant 4020, 1 phr of antioxidant RD, 3 phr of zinc oxide, 1 phr of stearic acid, 50 phr of white carbon black, 4 phr of silane coupling agent Si69 and 10 phr of aromatic oil were mixed in an internal mixer at 100±5° C. for 6 minutes to obtain an internal mixer;

[0143] (2) Mix the rubber at 140±5°C for 5 minutes;

[0144] (3) mixing the internal rubber and the vulcanizing agent in an open mixer, and thinning the mixture 5 times before sheeting to obtain a mixed rubber;

[0145] (4) The mixed rubber is vulcanized at a specific t90, 160°C to obtain a vulcanized rubber, i.e., composite material 7.

[0146] The tensile strength test results show that when 2.5phr modified aramid nanocomposite filler e is added to the silica reinforced polymer matrix, the tensile strength of the composite material is increased by 5.3%, the 300% elongation stress is increased by 7.1%, and the DIN abrasion is increased by 4.2% because no water-soluble polymer is added during the preparation of the modified aramid nanocomposite filler e.

[0147] like Figure 4As shown in (b), the scanning electron microscopy of the brittle fracture surface of the composite material shows that although the dispersion of the modified aramid nanofibers in the polymer matrix has improved, there are some interface interaction defects, resulting in insignificant performance improvement.

[0148] In summary, by comparing the results of the embodiments and the comparative examples, it can be clearly observed that the powdered modified aramid nanocomposite filler prepared by the modification method of the present invention overcomes the chemical inertness of aramid nanofibers and improves the agglomeration problem of aramid nanofibers. Secondly, in the obtained modified aramid nanocomposite filler / polymer composite material, the modified aramid nanofibers exhibit excellent dispersibility, and at the same time, the interface bonding effect between the modified aramid nanofibers and the composite polymer is significantly enhanced. Moreover, by adding a small amount of modified aramid nanocomposite filler, the physical and mechanical properties of the polymer composite material are significantly improved.

Claims

1. A method for preparing a powdered modified aramid nanocomposite filler, characterized in that: The preparation method of the modified aramid nanocomposite filler comprises the following steps: (1) adding a water-soluble polymer to a solvent A, stirring and dissolving the mixture to obtain a mixed solution A; (2) adding the aramid nanofiber hydrogel to the mixed solution A, adding the alkoxysilane compound during the stirring process, and continuing to stir evenly to obtain a mixed solution B; (3) dispersing the silicate compound in solvent B, adding the mixture to the mixed solution B, and continuing to stir the reaction to obtain a modified aramid nanocomposite filler dispersion with grafted functionalized silica nanoparticles; (4) After vacuum-assisted filtration of the modified aramid nanocomposite filler dispersion, the obtained solid is washed and placed in a vacuum oven for drying to obtain a powdered modified aramid nanocomposite filler.

2. The preparation method according to claim 1, wherein: In the step (1), the water-soluble polymer is a mixture of one or more strongly hydrophilic polymers containing polar nonionic groups; The diameter of the aramid nanofiber in the aramid nanofiber hydrogel is 10-300 nm, and the content of the aramid nanofiber is 1-10 wt %; The solvent A is a mixture of one or more of deionized water, ethanol, propanol, acetone, butanone, tetrahydrofuran, n-butanol, ethyl acetate, dimethylformamide, dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.

3. The preparation method according to claim 2, characterized in that: The strongly hydrophilic polymer includes polyethylene glycol monomethyl ether, polyethylene glycol, polyoxyethylene, and polyvinyl pyrrolidone.

4. The preparation method according to claim 1, wherein: In the step (2), the alkoxysilane compound is a mixture of one or more of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.

5. The preparation method according to claim 1, characterized in that: In the step (3), the silicate compound is a mixture of one or more of ethyl orthosilicate, butyl orthosilicate, propyl orthosilicate and isopropyl orthosilicate. The solvent B is a mixture of one or more of deionized water, ethanol, propanol, acetone, butanone, tetrahydrofuran, n-butanol, ethyl acetate, dimethylformamide, dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.

6. A powdery modified aramid nanocomposite filler, characterized in that: The functionalized silica nanoparticles are prepared by the preparation method described in claims 1-5.

7. The use of the powdered modified aramid nanocomposite filler according to claim 6 in the preparation of a modified polymer composite material, characterized in that: The polymer in the modified polymer composite material is a mixture of one or more polar or non-polar polymers.

8. Use of the powdered modified aramid nanocomposite filler in a polymer composite material according to claim 7, preferably, the polymer is at least one of polymers containing a benzene ring or a polar group.

9. Use of the powdered modified aramid nanocomposite filler according to claim 8 in a polymer composite material, more preferably, the polymer is a mixture of one or more polymers containing a benzene ring, an ester group, an ether group, a hydroxyl group, a cyano group, an amide group, a halogen group, a carboxyl group, and a carbonate group.

10. Use of the powdered modified aramid nanocomposite filler according to claim 9 in a polymer composite material, most preferably, the polymer is a mixture of one or more of styrene-butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, acrylic rubber, ethylene-vinyl acetate rubber, polycarbonate, polyurethane, polytetrafluoroethylene, epoxy resin, and polyvinyl alcohol.

Citation Information

Patent Citations

  • Nanocellulose composite filler as well as preparation method and application thereof

    CN115636986A

  • Bead-like aramid nanofiber and preparation method and application of composite material of bead-like aramid nanofiber

    CN115652628A

  • Preparation method of surface modified aramid nanofiber and application of surface modified aramid nanofiber in all-solid-state polymer electrolyte and lithium battery

    CN118326706A

  • Preparation method of modified aramid nanofiber and composite material and application thereof

    CN118374023A

  • Highly dispersible carbon NANO structures and method for preparation thereof, and polymer composite comprising the carbon NANO structures

    KR1020140134142A

Cited By

  • Preparation method of aramid nanofiber / polyurethane composite material

    CN120518993A